2022
DOI: 10.1097/ee9.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium in groundwater aquifers increases the risk of MAC pulmonary infection in O’ahu, Hawai’i

Abstract: Rationale: Hawai’i has the highest prevalence of nontuberculous mycobacterial (NTM) pulmonary disease in the United States. Previous studies indicate that certain trace metals in surface water increase the risk of NTM infection. Objective: To identify whether trace metals influence the risk of NTM infection in O’ahu, Hawai’i. Methods: A population-based ecologic cohort study was conducted using NTM infection incidence data from patients enrolled at Kaiser Permanente Hawai’i during 2005–2019. We obtained so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…This study confirms our previous findings, and further strengthens the evidence for the increased risk of NTM infection with vanadium and/or molybdenum that we have observed in both CF and non-CF populations. 17–20 Increasing concentrations of vanadium in Oregon surface water 19 and Hawai’i groundwater 20 were significantly associated with increased risk of MAC infection, while increasing concentrations of molybdenum in surface water in both Colorado 17,18 and Oregon 19 were significantly associated with increased risk of M. abscessus infection. Interestingly, in our current study, sulfate demonstrated the strongest risk association for MAC while vanadium was only borderline significant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study confirms our previous findings, and further strengthens the evidence for the increased risk of NTM infection with vanadium and/or molybdenum that we have observed in both CF and non-CF populations. 17–20 Increasing concentrations of vanadium in Oregon surface water 19 and Hawai’i groundwater 20 were significantly associated with increased risk of MAC infection, while increasing concentrations of molybdenum in surface water in both Colorado 17,18 and Oregon 19 were significantly associated with increased risk of M. abscessus infection. Interestingly, in our current study, sulfate demonstrated the strongest risk association for MAC while vanadium was only borderline significant.…”
Section: Discussionmentioning
confidence: 99%
“…While the database providing the patient data did not identify those individuals whose water source is groundwater rather than surface water, we observed that vanadium was highly associated with MAC infection in both Oregon surface water 19 and Hawaiian groundwater. 20 In both states, basalt is a primary rock formation, which contains high concentrations of vanadium. Ultimately as rocks weather and soil erodes, minerals, like molybdenum and vanadium, are naturally released into our waterways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations